Status Hukum Pemberlakuan Peraturan Pelaksana Undang-Undang Setelah Di Batalkannya Undang-Undang Oleh Mahkamah Konstitusi - Tarwin Idris (Universitas Islam Indonesia, 2020)
This study aims to analyze the legal status of implementing regulations for the Law after the Law gets annulled by the Constitutional Court, whether implementing the regulation still legally binding? This is a normative juridical legal research. The collection of legal materials is carried out through literature review, both primary and secondary legal materials. The results of this study conclude that the implementing regulations of the Law after the Law gets annulled by the Constitutional Court are no longer legally binding. This is because the Law, articles, or paragraphs that form the legal basis for the formation of the Implementing Regulations have been revoked or declared contradicting the 1945 Constitution of the Republic of Indonesia. Therefore, implementing regulations which contain material to implement the Law properly are also deemed contradictory with the 1945 Constitution of the Republic of Indonesia, it is on this basis that the Implementing Regulations are declared to no longer have binding legal force.